Lateralization and cognitive systems - Onur Gunturkun (Frontiers Research Topics, 2015)
Left-right asymmetries of structure and function are a common organization principle in the brains of humans and non-human vertebrates alike. While there are inherently asymmetric systems such as the human language system or the song system of songbirds, the impact of structural or functional asymmetries on perception, cognition and behavior is not necessarily limited to these systems. For example, performance in experimental paradigms that assess executive functions such as inhibition, planning or action monitoring is influenced by information processing in the bottom-up channel. Depending on the type of stimuli used, one hemisphere can be more efficient in processing than the other and these functional cerebral asymmetries have been shown to modulate the efficacy of executive functions via the bottom-up channel. We only begin to understand the complex neuronal mechanisms underlying this interaction between hemispheric asymmetries and cognitive systems. Therefore, it is the aim of this Research Topics to further elucidate how structural or functional hemispheric asymmetries modulate perception, cognition and behavior in the broadest sense.